Patterns of diversification amongst tropical regions compared: a case study in Sapotaceae - Armstrong, Kate E.; Stone, Graham N.; Nicholls, James A.; Valderrama, Eugenio; Anderberg, Arne A.; Smedmark, Jenny; Gautier, Laurent; Naciri, Yamama; Milne, Richard; Richardson, James E. (Frontiers in Genetics, 2014)
Species diversity is unequally distributed across the globe, with the greatest concentration occurring in the tropics. Even within the tropics, there are significant differences in the numbers of taxa found in each continental region. Manilkara is a pantropical genus of trees in the Sapotaceae comprising c. 78 species. Its distribution allows for biogeographic investigation and testing of whether rates of diversification differ amongst tropical regions. The age and geographical origin of Manilkara are inferred to determine whether Gondwanan break-up, boreotropical migration or long distance dispersal have shaped its current disjunct distribution. Diversification rates through time are also analyzed to determine whether the timing and tempo of speciation on each continent coincides with geoclimatic events. Bayesian analyses of nuclear (ITS) and plastid (rpl32-trnL, rps16-trnK and trnS-trnFM) sequences were used to reconstruct a species level phylogeny of Manilkara and related genera in the tribe Mimusopeae. Analyses of the nuclear data using a fossil-calibrated relaxed molecular clock indicate that Manilkara evolved 32-29 million years ago (Mya) in Africa. Lineages within the genus dispersed to the Neotropics 26-18 Mya and to Asia 28-15 Mya. Higher speciation rates are found in the Neotropical Manilkara clade than in either African or Asian clades. Dating of regional diversification correlates with known palaeoclimatic events. In South America, the divergence between Atlantic coastal forest and Amazonian clades coincides with the formation of drier Cerrado and Caatinga habitats between them. In Africa diversification coincides with Tertiary cycles of aridification and uplift of the east African plateaux. In Southeast Asia dispersal may have been limited by the relatively recent emergence of land in New Guinea and islands further east c. 10 Mya.